The science in foods - Ng, Karen; Boland, Michael; Leigh, Richard; Classroom Video (Australia : Classroom Video, 2006)
This program introduce students to the science behind the food we eat. start by describing what food is, the components found in food and why we need carbohydrates, proteins, vitamins and minerals
Title from title screen
Title from title screen
Executive producer, Mark McAuliffe ; graphic, Paul Sutherland ; camera, Karen Ng
Voice over: Mark Collard
Keywords: Food -- Analysis; Food -- Composition; Food